THE TABULAR OF CRYPTOGRAPHIC PRIMITIVES OF NONLINEAR SUBSTITUTIONS (Journal of Information Technologies in Education (ITE), 2015)
Classic primitives nonlinear substitution is a simple replacing each character encrypted text on a fixed symbol of the same alphabet, actually realizing the transformation one alphabet simple substitution cipher. And as a consequence - the entropy cipher text coincides with the entropy of the source text. The paper discusses the various options for randomization primitives nonlinear substitution in the results, those who achieved a significant increase in the entropy of the output text, with the cryptograms acquires properties similar to those of white noise.
Keywords: cryptographic primitive; non-linear substitution; randomization